Proprotein Convertase Subtilisin/Kexin Type 9 Induction in COVID-19 Is Poorly Associated with Disease Severity and Cholesterol Levels - Patricia Mester; Pablo Amend; Stephan Schmid; Jürgen J. Wenzel; Marcus Höring; Gerhard Liebisch; Sabrina Krautbauer; Martina Müller; Christa Buechler; Vlad Pavel (MDPI AG, 2024)
SARS-CoV-2 infection was shown to induce proprotein convertase subtilisin/kexin type 9 (PCSK9) plasma levels in sepsis. Here, we investigate the association between serum PCSK9 levels and disease severity. PCSK9 was measured in serum of 55 controls, 40 patients with moderate and 60 patients with severe COVID-19 disease. Serum PCSK9 was elevated in moderate COVID-19 compared to controls and further increased in severe cases. PCSK9 levels were not associated with C-reactive protein, bacterial superinfections, interventions, or survival in patients with severe COVID-19. PCSK9 regulates circulating cholesterol levels, and 15 cholesteryl ester (CE) species and free cholesterol (FC) were quantified by direct flow injection analysis using a high-resolution hybrid quadrupole-Orbitrap mass spectrometer. Most CE species with shorter fatty acid chains were decreased in severe compared to moderate COVID-19, and none of the CE species were correlated with PCSK9 in patients with severe COVID-19. Levels of all CE species negatively correlated with C-reactive protein in severe COVID-19 patients. Notably, FC was induced in severe compared to moderate COVID-19. The FC/CE ratio correlated positively with inflammatory markers and was associated with non-survival. The current study suggests that the imbalance between CE and FC levels is associated with disease severity and mortality in patients with COVID-19.